PERANCANGAN SISTEM INFORMASI PENJUALAN KERTAS MENGGUNAKAN MICROSOFT VISUAL STUDIO 2010 DAN DATABASE MYSQL DI PT. PERURI KERTAS PADALARANG BANDUNG - Aldy Ardiansyah (POLITEKNIK PIKSI GANESHA, 2021)
The purpose of the research is design of sales information systems for expenditures using microsoft visual studio 2010 and mysql database in PT. PERURI KERTAS Padalarang Bandung. The method of the research is the descriptive qualitative to find out the facts and actual data that occurred in PT. PERURI KERTAS, the methods of collection data is observation, interviews, and literature study related to the subject matter. The development method used the Waterfall Model. Design of the sales information system uses the Microsoft Visual Studio 2010 as programming language with MySQL Database. Sales Information System rans on PT. PERURI KERTAS has used a computer-based system. Information systems was running have experienced a decline in the quality of information, the responsiveness of data processing takes a long time. To overcome this problem, the authors provide a suggestion to designing a sales information system that is newer, more responsive data processing and can also following the technological developments for the operating system and the devices it uses without forgetting the function of the sales information system.